A path for evaluating the mechanical response of rock masses based on deep mining-induced microseismic data: A case study. (September 2021) - Zhao, Yong; Yang, Tianhong; Liu, Honglei; Wang, Shuhong; Zhang, Penghai; Jia, Peng; Wang, Xinrong
Highlights: A set of methods was developed for evaluating the mechanical response of surrounding rocks using microseismic data. A new damage model was proposed based on mining-induced fractures inferred from microseismic data. The combination of microseismic monitoring and numerical simulation is benefit to evaluate the stability of the stope. Abstract: Deep, high-intensity mining has become a general development trend in mineral resource extraction operations. Under deep mining conditions, high-intensity mining renders the mechanical environment more complicated. The strong disturbance caused by excavating ore-bearing rocks may trigger ground-pressure-induced disasters, and the associated disaster mechanism is more complex. In the mining of deep metal orebodies, stope stability has been a crucial factor restricting mining safety. In response to the above problems, a path for evaluating the mechanical response of surrounding rocks using mining-induced microseismic (MS) data was proposed and applied to a test stope of the Xiadian Gold Mine, which has experienced stope instability as a result of deep mining. First, MS data received before, during, and after the mining of the test stope were analyzed to explore the evolution of MS events, the failure mechanism, and the evolution of fractures during different stages. Subsequently, by utilizing the method for calculating the damage, seismic stress, and seismic strain defined by the moment tensor (MT), the dynamic response trends of damage, stress, and strain during the mining of the test stope were investigated. Finally, the proposed damage model based on fractures derived from MS data was mapped into a finite element numerical analysis. According to the time sequence of the stope mining, the rock mass parameters were dynamically weakened to investigate the changes in the plastic zone and the displacement of the test stope under the original and new stope structures and determine the stability of surrounding rocks under the new stope structure. The research is expected to aid in the mining design and support design of deep mines and provide a reference for the same type of mines elsewhere.